Overview of the Sanitary and Phytosanitary Measures in QUAD Countries on Tropical Fruits and Vegetables Imported from Developing Countries - Ellen Pay (South Centre, 2005)
A number of developing countries,1 and especially least developed countries (LDCs), rely on agriculture for their food security, export earnings and rural development. It has been estimated that the agricultural sector accounts for between 30 per cent and 60 per cent of gross domestic product (GDP) for many of these countries, and is the major source of foreign exchange. The Food and Agriculture Organization of the United Nations (FAO) (2002) noted that the economies of many developing countries depend on the exports of one or a few commodity exports, making them particularly vulnerable to price variations on specific commodities. It noted that single commodity-dependence is more pronounced in tropical regions, and notably so for specific tropical products including sugar, coffee, bananas, cotton lint and cocoa beans. The variability and decline of commodity prices is well documented (FAO, 2005). It erodes the competitiveness of commodities exported from non-subsidizing developing countries, discourages investment and expansion of their food exporting sectors and, in the event that developing countries depend heavily on agricultural exports, worsen their terms of trade. According to the FAO's State of Agricultural Commodity Markets (2005), the variability and decline in international agricultural commodity prices has serious implications for developing countries that are highly dependent on commodity export earnings, especially from traditional tropical crops. Since tariff escalation in agricultural markets is regarded as one of the major factors hindering the processing of traditional products for export, analysts have explored the potential for exporting non - traditional fresh fruits and vegetables to QUAD countries (Canada, the EU, Japan and the United States). These are valid alternatives because first, tropical fruits and vegetables are not usually cultivated in QUAD countries and therefore, their trade is not distorted by domestic producer support measures. Secondly, consumer tastes in QUAD countries are diversifying into 'exotic' tropical fruits and vegetables. The FAO for example, is currently helping market players to develop international trade for organic mangoes and pineapples produced in Sub-Saharan Africa.
Keywords: 300; Agriculture; Commodities; Food Security; GATT; Import Surge; Least Developed Countries (LDCs); Tariffs; World Trade Organization (WTO)